Analisis microbiologico de coliformes totales y fecales en muestras de agua de mar extraidas de los balnearios de Salaverry - Huanchaco en los meses noviembre - diciembre 2015 - Carranza León, Vanessa Milagros (2016)
This research aimed to evaluate the microbiological quality of seawater from the beaches of Salaverry and Huanchaco during 2015. The evaluation was conducted in the months of November and December, performing sampling each week of the aforementioned beaches. Water samples were obtained based on the guidelines given by AWWA, APHA and WEF (2012) in terms of quantity, harvesting, storage and transport to the laboratory, as well as handling for examination. Regarding the microbiological analysis, certain parameters were total coliforms and fecal coliforms. The average for total coliforms in Huanchaco was higher than the average of total coliform spa Salaverry. The averages of Total Coliform for the month of November (Table 2 and Figure 3) between the resorts of Huanchaco and Salaverry were 461.5 MPN / 100 ml and 14.0 MPN / 100 ml respectively, being those values within the provisions of national standards environmental quality standards for water recreation (maximum total coliform 1000 NMP / 100 ml fecal coliform maximum 200 MPN / 100 ml) From the results obtained in relation to the presence of total and fecal coliforms it can be concluded that there is a greater presence in Huanchaco in Salaverry by counting the first with the largest crowd of bathers, however presents a greater risk of contamination for the community who go to this beach